Using Ultrasonic Waves to Determine the Microstructure of Snow - Lieblappen, Ross; Fegyveresi, John M.; Courville, Zoe; Albert, Donald G. (Frontiers in Earth Science, 2020)
High frequency (ultrasonic) acoustic wave propagation measurements were inverted to determine important near-surface parameters of snow including porosity, tortuosity, and pore geometry, using a newly-designed, oblique-reflection transducer apparatus. Acoustic signals interact with the physical structure of porous media, are particularly sensitive to porosity and tortuosity, and can be used to measure physical properties in a non-destructive manner. Given the fragile nature of freshly fallen snow, non-contact, non-destructive characterization methods made possible via acoustic signals, are desirable. High frequency wave propagation methods can be used to determine in situ near surface micro-pore geometry parameters in snow using methods demonstrated on cohesive porous materials including manufactured foams, porous metals, and sintered glass beads. Here, we conducted high frequency, oblique-angle and near vertical reflection measurements on snow samples to demonstrate the feasibility of acoustic response detection. We compared the acoustically derived snow physical parameters, including porosity and tortuosity, with values determined from X-ray micro-computed tomography (μCT) and gravimetric methods. Preliminary results using different snow types, and following the methods from previous work for cohesive porous media (i.e. fused glass beads) show good agreement between values of porosity determined from the acoustic measurements and the values determined from μCT image analysis.